الثقافة المقاولاتية لدى الطالب الجامعي - باي، صهيب, بن عمارة، ياسين (جامعة الوادي university of Eloued, 2021)
الملخص : أصبح موضوع المقاولاتية وإنشاء المؤسسات يحتل حيزا كبيرا من إهتمام الحكومات والعديد من الدول، ولأن الكم الهائل للطلبة المتخرجين في السنوات الأخيرة أصبح يفرض على كاحل الدولة إيجاد حلول في الميدان المقاولاتي لتشغيل المتخرجين وضمان منصب شغل لهم، وهو ما دفعنا للبحث حول هذه المشكلة حيث تعالج واقع تصور الثقافة المقاولاتية لدى الطلبة الجامعيين ومدى تقبلهم وتشجعهم للدخول في ميدان المقاولاتية وإنشاء المشاريع والمؤسسات والاستفادة من مختلف اشكال الدعم من قبل الدولة ومنه تكريس مكونات الثقافة المقاولاتية لديهم و كذلك رصيدهم العلمي المقاولاتي في تكوين مشروع مقاولاتي ناجح. The issue of entrepreneurship and the establishment of institutions has become of great interest to governments and many countries, and because the huge number of students graduating in recent years has become imposed on the state’s shoulders to find solutions in the entrepreneurial field to employ graduates and secure a job for them, which prompted us to search for this problem, as it addresses the reality The perception of entrepreneurship culture among university students and the extent to which they accept and encourage them to enter the field of entrepreneurship, establish projects and institutions, and benefit from various forms of support from the state, including dedicating the components of their entrepreneurial culture, as well as their entrepreneurial scientific credit in forming a successful entrepreneurial project.
دراسة ميدانية بثانوية السعيد عبد الحي بالوادي
مذكرة ماستر علم اجتماع تخصص تنظيم وعمل
Keywords: المقاولاتية; Entrepreneuriat; Entrepreneurship